2020
DOI: 10.1016/j.vgie.2020.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Safety of EUS-guided gallbladder drainage using a lumen-apposing metal stent in patients requiring anticoagulation

Abstract: Background and Aims: EUS-guided gallbladder drainage (EUS-GBD) can be used to treat acute cholecystitis in patients with medical comorbidities that prevent definitive operative management. Historically, nonsurgical management of cholecystitis was achieved by way of percutaneous gallbladder drainage. Methods: We examined the periprocedural bleeding rate of EUS-GBD for acute cholecystitis using lumenapposing metal stents in 5 high-surgical-risk patients requiring anticoagulation. Data on 5 nonoperative candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, the rate of bleeding and perforation was significantly higher for EUS-GBD, compared to PGBD and TGBD (4.3% vs. 2% vs. 1.9%, p =0.02, for bleeding; 3.7% vs. 2% vs. 2%, p = 0.04, for perforation). EUS-GBD should be considered a high-risk procedure in terms of bleeding; therefore, anti-thrombotic drugs should be managed accordingly, even though successful and uneventful EUS-GBD has been anecdotally reported as a last resource in patients with coagulopathy or on anticoagulation therapy [46,47]. On the other hand, PGBD has an increased risk of stent migration/dislodgement and a higher overall adverse events risk according to another recent meta-analysis [40,48].…”
Section: Gallbladder Drainage In Acute Cholecystitis: Percutaneous Tr...mentioning
confidence: 99%
“…However, the rate of bleeding and perforation was significantly higher for EUS-GBD, compared to PGBD and TGBD (4.3% vs. 2% vs. 1.9%, p =0.02, for bleeding; 3.7% vs. 2% vs. 2%, p = 0.04, for perforation). EUS-GBD should be considered a high-risk procedure in terms of bleeding; therefore, anti-thrombotic drugs should be managed accordingly, even though successful and uneventful EUS-GBD has been anecdotally reported as a last resource in patients with coagulopathy or on anticoagulation therapy [46,47]. On the other hand, PGBD has an increased risk of stent migration/dislodgement and a higher overall adverse events risk according to another recent meta-analysis [40,48].…”
Section: Gallbladder Drainage In Acute Cholecystitis: Percutaneous Tr...mentioning
confidence: 99%
“…2 of 9 one step. Numerous studies have now demonstrated EUS-GBD with LAMS to be safe and effective in poor operative candidates [15][16][17][18]. In a recent systematic review and metaanalysis, EUS-GBD with LAMS demonstrated rates of technical success, clinical success, and adverse events of 94.7%, 92.1%, and 11.7%, respectively [19].…”
Section: Introductionmentioning
confidence: 99%
“…The application of LAMS for EUS-GBD has drastically simplified the procedure as stent insertion can be performed in just one step. Numerous studies have now demonstrated EUS-GBD with LAMS to be safe and effective in poor operative candidates [15][16][17][18]. In a recent systematic review and meta-analysis, EUS-GBD with LAMS demonstrated rates of technical success, clinical success, and adverse events of 94.7%, 92.1%, and 11.7%, respectively [19].…”
Section: Introductionmentioning
confidence: 99%